Reformasi Pengelolaan Migas dengan Vertical Integrated System guna Mewujudkan Kesejahteraan Berdasarkan Konstitusi - Istata Luqman Adhicahyono; Sumyati Sumyati; Aditya Bagus Herlambang; Sukinta Sukinta; Muhamad Azhar (Administrative Law and Governance Journal, 2021)
Abstract This study aims to determine the Reform of Oil and Gas Management with a Vertical Integrated System to Realize Welfare Based on the Constitution. The approach method used in this research is the Legal Research approach, the research is obtained from library research and legal documents, which means that the research is carried out by reviewing library data and existing references. The results of the research show that first, the oil and gas management system through open access and unbundling that is currently being implemented is the result of the implementation of Law No. 22 of 2001 concerning Oil and Gas, this system is contrary to the constitutional mandate, namely Pancasila. Second, the management of oil and gas through a vertical integrated system can be a means for the welfare of the Indonesian people, this system is a solution to solve oil and gas management problems in Indonesia, the vertical integrated system is a system that has triumphed in the new order era, Keywords: Oil and Gas, Governance, Welfare, Constitution AbstrakPenelitian bertujuan untuk mengetahui Reformasi Pengelolaan Migas dengan Vertical Integrated System guna Mewujudkan Kesejahteraan Berdasarkan Konstitusi. Metode pendekatan yang digunakan dalam penelitian ini adalah metode pendekatan Legal Research, penelitian didapat dari library research dan legal document, yang artinya penelitian dilakukan dengan mengkaji data-data pustaka dan referensi-referensi yang ada. Hasil penelitain menunjukan bahwa pertama, Sistem pengelolaan migas melalui open access dan unbundling yang diberlakukan sekarang merupakan akibat dari implementasi UU No.22 tahun 2001 tentang Minyak dan Gas, sistem ini bertentangan dengan amanat konstitusi yaitu Pancasila. Kedua, Pengelolaan migas melalui vertical integrated system dapat menjadi sarana mensejahterkan rakyat Indonesia, sistem ini merupkan solusi untuk memecahkan masalah pengelolaan migas di Indonesia, vertical integrated system merupakan sistem yang pernah berjaya di masa orde baru, Kata Kunci: Minya dan Gas, Tata kelola, Kesejahteraan, Kontitusi